Life Cycle Analysis (LCA) of Halal authentication approaches on industrial food waste for gelatine production: a mini review - Mohd Daud, Nurul Iman; Ahmad Tajuddin, Husna; Mansor, Mariatul Fadzillah; Nordin, Noor Faizul Hadry (International Institute for Halal Research and Training (INHART), International Islamic University Malaysia, 2023)
Industrial food waste is a major issue that affects numerous countries. One of the techniques to reduce the generation of food waste is to recycle it for other purposes. Particularly, food waste from livestock industries can be utilised for gelatine preparation. However, the study on halal authentication of industrial food waste is still low. This review is conducted to identify the available protein analysis methods utilised in halal authentication of industrial food waste. It is also to compare and acknowledge the most reliable method. This review is performed in three steps: the planning phase, the conducting phase and the analysing phase. Reliable methods such as polymerase chain reaction (PCR), multiple reaction monitoring (MRM), fluorescent molecularly imprinted polymer nanogel (F-MIP-NG), lateral flow devices (LFDs) and loop-mediated isothermal amplification (LAMP) are identified and discussed. Their sensitivity limits are also recognised and compared.